2006
DOI: 10.1080/15216540500531705
|View full text |Cite
|
Sign up to set email alerts
|

Mining for allosteric information: Natural mutations and positional sequence conservation in pyruvate kinase

Abstract: Although the amino acid sequences and the structures of pyruvate kinase (PYK) isozymes are highly conserved, allosteric regulations differ. This suggests that amino acids with low conservation play important roles in the allosteric mechanism. The current work exploits a 'natural screen'‐ the 122 point mutations identified in the human gene encoding the erythrocyte PYK isozyme and associated with nonspherocytic hemolytic anemia ‐ to learn what amino acid positions in PYK may be important for allosteric regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 38 publications
(28 reference statements)
0
41
0
Order By: Relevance
“…The site point mutation data presented here for LmPYK and for a number of other PYKs 25 show that profound changes in enzymatic activity can be achieved by a broad variety of mutants remote from the active site or the effector site. In the above example, mutations in the large interface are some 30 Å away from the binding site where the effects are observed.…”
Section: Pyk May Have a Dynamic Mechanism Of Activationmentioning
confidence: 92%
See 1 more Smart Citation
“…The site point mutation data presented here for LmPYK and for a number of other PYKs 25 show that profound changes in enzymatic activity can be achieved by a broad variety of mutants remote from the active site or the effector site. In the above example, mutations in the large interface are some 30 Å away from the binding site where the effects are observed.…”
Section: Pyk May Have a Dynamic Mechanism Of Activationmentioning
confidence: 92%
“…Of potential medical interest are the 122 naturally occurring mutations that have been identified in human erythrocyte PYK and are linked to the disease nonspherocytic haemolytic anemia. 25 A number of these mutations, occurring mainly in the C domain, are not highly conserved over the 241 species and isoforms examined and are therefore hypothesised to play a role in allostery.…”
Section: Introductionmentioning
confidence: 99%
“…The 6 o rigid body rocking motion (Fig. 2e) of LmPYK moves a crucially important Arg 310 side chain (mutation of the equivalent Arg in E. coli PYK results in total inactivity (32), and a mutation to either Lys or Trp results in PYK deficiency in humans (19)) into the vicinity of the active site of the adjacent subunit (Fig. 2b), where it forms two stabilizing hydrogen bonds with the backbone carbonyls (residues Arg 262 and Gly 263 ) belonging to the oxalate (phosphoenolpyruvate)-stabilized A␣6Ј helix.…”
Section: Resultsmentioning
confidence: 99%
“…For example, as discussed by del Sol et al (13), the plasticity within an allosteric response is such that nearby residues can easily functionally substitute for one another. Related, it has been shown in several systems (e.g., pyruvate kinase (59)) that mutations at highly variable positions distal to the active site can have dramatic impacts on catalytic activity. As such, based on the ubiquitous diversity of allosteric mechanisms, Kuriyan and Eisenberg (43) have intriguingly suggested that allosteric diversity is responsible for the complexity of life.…”
Section: A Critical View Of the Underlying Concept Of Conserved Allosmentioning
confidence: 98%